Diagnosis and evaluation of mitral valve disease using transseptal Doppler ultrasound catheterization. Issue 3 (March 1975) - Kalmanson, D; Veyrat, C; Bernier, A; Savier, C H; Chiche, P; Witchitz, S
Abstract : In 33 patients with confirmed mitral valve disease, the mitral valve flow velocity traces were recorded by means of a directional Doppler ultrasonic velocimeter using the transseptal route, and correlated with the clinical and haemodynamic data. In all cases, characteristic anomalies of the mitral flow velocity patterns were noted and could be related to the type of lesion, stenosis, regurgitation, or a combination of these. Furthermore, specific patterns of the flow velocity traces were shown to correlate satisfactorily with the degree of severity of the disease. The authors propose a pathophysiological interpretation of the anomalies of the velocity patterns, based on turbulence for stenosis and backward flow wave for regurgitation. They conclude that the transseptal directional Doppler catheterization provides a new reliable method for establishing the diagnosis and grading the severity of mitral valve disease using pattern recognition, and, moreover, offers a new approach to the understanding of mitral haemodynamic disturbances on a beat-to-beat basis.